The synthesis of ensemble of binary manipulated radio signals of the difficult form by means of indirect frequency synthesizers (part I) - Сыроветник, Владислав Сергеевич (Eastern-European Journal of Enterprise Technologies, 2012)
There is considered an approach to the synthesis of the complex form signals, representing radio impulses with complex angular modulation, formed by the indirect FS for forming of ensemble of binary manipulated radio signals.